Overview Independence and Cognitive Function of Elderly - Yulia Susanti; Livana PH (GLOBAL HEALTH SCIENCE GROUP, 2019)
Elderly is not a disease, but is an advanced stage of a life process characterized by a decrease in the body's ability to adapt to environmental stress. Elderly causes anatomical, physiological, and biochemical changes in the body, so that it will affect the overall function and ability of the body. The study aims to determine the picture of independence and cognitive function in the elderly. The study used a descriptive method with a sample of 108 elderly in the City of Kendal Indonesia. Data were analyzed using frequency distribution. The results showed the majority of respondents (81.5%) elderly were categorized as having the ability to independently level and 78.6% had normal cognitive function, 18.5% had mild cognitive impairment, and 1.9% had severe cognitive impairment. Keywords: independence, cognitive function, elderly